On Analyzing the Correlations and Implications of Single-Number Quantities for Rating Airborne Sound Insulation in the Frequency Range 50 Hz to 5 kHz. Issue 1 (March 2015) - Garg, N.; Maji, S.
The paper presents the implications and correlations of single-number quantities ( SNQ ) proposed by Scholl et al ., 2011 calculated from the sound transmission loss measurements conducted in the extended frequency range of 50 Hz to 5 kHz. Although the new SNQ proposed in ISO 16717 have been withdrawn, yet these SNQ may appear in future which has prompted the present analysis and discussion. The present study contributes to the ongoing debate on newly proposed SNQ by establishing their implications and correlations and the shift in numerical values in transition from old to proposed SNQ .